Relationship between structural changes in the myocardium of the left atrium and the effectiveness of cryoablation in persistent atrial fibrillation - V. S. Kirilova; O. V. Stukalova; O. P. Aparina; E. B. Maykov («REMEDIUM GROUP» Ltd., 2023)
Introduction. High-resolution contrast-enhanced cardiac magnetic resonance imaging reveals left atrial fibrosis, the severity of which may be related to the effectiveness of catheter ablation.Aim. To study the structural changes of the left atrium myocardium according to magnetic resonance imaging with contrast in patients with persistent atrial fibrillation before balloon cryoablation and compare the results with the effectiveness of the intervention.Materials and methods. The study included 89 patients with persistent form of atrial fibrillation. The patients were randomized into two groups: in the 1st, the pulmonary veins cryoablation was performed (n = 39 (53.4%)); in the 2nd, the pulmonary veins and posterior wall of the left atrium cryoablation was performed (n = 34 (46.6%)). All patients before cryoablation underwent cardiac magnetic resonance imaging with delayed contrast using a high-resolution MR pulse sequence. The clinical efficacy of the intervention was evaluated after 12 months after the cryoablation.Results. The severity of fibrotic myocardial lesion of the left atrium before balloon cryoablation was 0.7% [0; 3,07]. Overall efficiency of the intervention rate was 57.1%. Cryoablation was most effective (59.5%) in patients severity of fibrosis less than 20% and least effective (50%) severity of fibrosis more than 20%. Risk factors for atrial fibrillation recurrence after cryoablation were: early atrial fibrillation recurrence, female sex, the maximum atrial fibrillation duration more than 3 months, stroke/TIA.Conclusion. The severity of left atrial fibrosis more than 20%, early recurrence of atrial fibrillation in the first 3 months after the cryoablation, female sex, the duration of the maximum atrial fibrillation episode more than 3 months, and a history of stroke/transient ischemic attack may be associated with recurrence of AF during the period observation 3-12 months.